Clinical and pathological characteristics of familial melanoma with germline TERT promoter variants. (16th August 2022) - Zaremba, Anne; Meier, Friedegund; Schlein, Christian; Jansen, Philipp; Lodde, Georg; Song, Mingxia; Kretz, Julia; Möller, Inga; Stadtler, Nadine; Livingstone, Elisabeth; Zimmer, Lisa; Hadaschik, Eva; et al.
Abstract: Around 10% of melanoma occurs in patients with a suspected familial predisposition. TERT promoter mutations are the most common somatic hotspot mutations in human cancers. However, only two families with germline mutations have been identified to date. We present detailed histological, clinical, and molecular pathologic analyses of affected patients and details of newly identified individuals in one of these previously reported families. TERT (NM_198253.3) Chr.5:1, 295, 161T>C (c.‐57 T>C) promoter variants were detected in all melanoma‐affected ( n = 18) and one non‐diseased family member. The median age at diagnosis was 30 years ( n = 18, range 16–46 years, 2 unknown). While most primary melanomas arose on the upper extremities ( n = 7, 21%) and were superficial spreading melanoma (SSM, n = 8, 24%), many primary melanomas also originated from non‐UV‐exposed mucosal ( n = 2, 6%) and acral ( n = 4, 12%) locations. One SSM sample harbored a Chr.5:1, 295, 228C>T TERT promoter mutation in addition to the germline Chr.5:1, 295, 161T>C variant, arguing additional pathway activation can support tumor pathogenesis. Patients treated with BRAF inhibitor and/or immune checkpoint inhibition (ICI) showed responses, although of limited duration. One mucosal melanoma harbored both a KIT copy number gain and an activating c.1727 p.Leu576Pro mutation. Following the modest response to ICI, subsequent KIT inhibitor (imatinib) therapy demonstrated an ongoing complete pathological response (currently 7 months).